Synthesis, Anticonvulsant and Binding Interaction Study of Novel Piperamides with Bovine Serum Albumin by Fluorescence Spectroscopy - K. Prashanth, Maralekere; N. Deepakumari, Hemavathi; S. Raghu, Madihalli; D. Revanasiddappa, Hosakere; Veeresh, Bantal (Central Nervous System Agents in Medicinal Chemistry, 2016)
A series of piperamides (PA) 8a-j were designed, synthesized and evaluated for their antimicrobial and anticonvulsant activity. Compounds 8a and 8h showed considerable antibacterial activity against B. subtilis with minimum inhibitory concentration (MIC) of 8 and 10 μg/mL, respectively. Compounds 8a and 8h showed advanced anticonvulsant activity as well as lower neurotoxicity than the reference drugs. The interaction between bovine serum albumin (BSA) and PA was investigated using fluorescence quenching and UV-vis absorption spectroscopy. Results showed that PA could strongly quinch the intrensic fluorescence of BSA through a static quencing procedure. The binding constant and number of binding sites of PA with BSA were obtained. The binding distance was calculated based on Forster non-radiative energy transfer theory.
Keywords: piperamide